2018
DOI: 10.1080/0142159x.2018.1457212
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ professional identity development from being actors in an objective structured teaching exercise

Abstract: Taking part in OSTEs as a simulated resident has a positive impact on students' vision regarding the institution as a learning environment and their own role by actively seeking or giving feedback. OSTEs support their professional identity development regarding learning and teaching while sustaining faculty development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Residents indicated that these relationships were important, but were superseded by professional commitments that caused the residents to mimic the hierarchy reinforced at work. However, in other studies, students felt a sense of agency to negotiate their identity, 72 especially as they conceptualised themselves from an outside perspective, 79,124 such as when learners thought through the matter of who was responsible for their learning 80 . Further, Joseph et al’s 119 work noted how incongruence of identities can lead to identity dissonance, a theme that was further explored in work by Kluijtmans et al 47 and Tahim, 126 which described PIF in physicians with dual professional identities and the challenges experienced by such physicians in having to straddle two professions.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Residents indicated that these relationships were important, but were superseded by professional commitments that caused the residents to mimic the hierarchy reinforced at work. However, in other studies, students felt a sense of agency to negotiate their identity, 72 especially as they conceptualised themselves from an outside perspective, 79,124 such as when learners thought through the matter of who was responsible for their learning 80 . Further, Joseph et al’s 119 work noted how incongruence of identities can lead to identity dissonance, a theme that was further explored in work by Kluijtmans et al 47 and Tahim, 126 which described PIF in physicians with dual professional identities and the challenges experienced by such physicians in having to straddle two professions.…”
Section: Resultsmentioning
confidence: 96%
“…Evidence found in Wong et al’s 53 analysis of written reflections highlighted how social interactions, role models and patient encounters influence PIF. Others found that the tone in which feedback is delivered influences what participants hear 80 . Several articles 50‐52,70 examined how longitudinal integrated clerkships afforded students safe environments in which to foster emerging identities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations